Response of PM2.5 Concentrations at the GAW Bukit Kototabang Station to ENSO Phases Based on Superimposed Epoch Analysis - Dodi Saputra; Nofri Yendri Sudiar; Dhiyaul Qalbi; Aditya Prapanca (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
This study aims to analyze the response of PM2.5 concentrations and rainfall to the El Niño and La Niña phases at the Global Atmosphere Watch Bukit Kototabang station, West Sumatra, using the Superposed Epoch Analysis method. Observational data of PM2.5 from the Beta Attenuation Monitor 1020, rainfall from the Automatic Agroclimate Weather Station, and sea surface temperature in the Niño 3.4 region were analyzed for the period October 2021 to May 2025. A total of 31 extreme rainfall events were identified as reference points (epochs) and classified into El Niño and La Niña periods. The results show that during the La Niña phase, an average rainfall increase of 41.1 mm effectively reduces PM2.5 concentration anomalies by approximately ±3.1 µg/m³. In contrast, during the El Niño phase, although rainfall increases by 33.5 mm, PM2.5 concentrations remain highly variable, with anomaly increases of approximately ±1.3 µg/m³, due to drier air masses and lower rainfall intensity. The combined results of SEA analysis and the Monte Carlo test indicate a 13-day SST lead during the El Niño period and a 9-day lag during the La Niña period. This study reveals that ENSO influences both rainfall and air quality at the GAW Bukit Kototabang station.